Highlights of IFPRI’s research and partnerships in Bangladesh 2012: Reducing poverty and hunger through food policy research - International Food Policy Research Institute (International Food Policy Research Institute, 2012)
Since its independence in 1971, Bangladesh has made enormous progress in food production, market development, employment growth, and social protection programs targeted to the poor. The nation has transformed itself from a country of chronic food shortages to a country of food self-sufficiency. It has successfully increased secondary school enrollment by using one of the earliest conditional cash transfer programs in existence. Since 1988, IFPRI has had a strong presence in the country, conducting food policy research, providing policy support, and strengthening stakeholders’ capacity. This on-the-ground presence has allowed IFPRI to generate evidence-based research results on critical on-going food security issues as well as on major unforeseen events— such as the 1998 floods that ravaged the country’s rice supply. Since 2010, IFPRI has scaled up its support to Bangladesh with the Policy Research and Strategy Support Program, which provides policy options and advisory services to the country’s policymakers. This brochure highlights some of IFPRI’s major projects in Bangladesh during the past few decades, and describes major new initiatives with the potential to positively influence food security policies that benefit the poorest.